Evaluating and Improving Stakeholder Accessibility of the World Health Organization's Tuberculosis Guidelines - Matthews, Micayla (My University, 2021)
Background: Tuberculosis (TB) is the leading cause of death from a single infectious agent worldwide. The World Health Organization’s (WHO) Global Tuberculosis (GTB) Programme issues evidence-informed guidelines with recommendations on TB. In an effort to improve the accessibility and use of these guidelines, we developed a new digitized WHO eTB catalogue of recommendations. Objective: The objective of this thesis was to explore stakeholder engagement with WHO TB recommendations. We sought to compare the accessibility of the WHO eTB catalogue to the conventional method of accessing WHO TB recommendations, and to explore the ways in which stakeholder feedback could be incorporated into quality improvement frameworks. Methods: We conducted a two-arm superiority randomized controlled trial through a survey among stakeholders who were past or planned future users of TB guidelines, recommendations, or policy advice. Using a 1:1 ratio, we randomly assigned participants to complete an activity using WHO eTB or the conventional website. We compared outcomes of accessibility, understanding, satisfaction and preference between groups. We incorporated qualitative feedback from free-text boxes into a quality improvement framework. Results: From February 26 to March 24 , 2021, we received 188 survey responses, 110 participants were randomized, and 102 were included in the interim analysis. On average, participants rated the WHO eTB catalogue as more accessible across four domains when compared to the WHO TB website. There was no difference in participant understanding of recommendation strength and certainty, but the ability to locate evidence to decision tables favored WHO eTB. We also received 75 qualitative responses, 47 of which yielded five themes: purpose, navigation, presentation, organization, and outreach. Conclusions: The WHO eTB catalogue of recommendations improved the accessibility of WHO TB recommendations and supporting evidence for stakeholders of interest. Our findings support the continued use, promotion, and quality improvement of the WHO eTB catalogue in the future.
Keywords: Guideline; Recommendation; Tuberculosis; GRADE; Evidence-Based Practice; Evidence to Decision Table